Rates of Breakthrough Reactions in Inpatients at High Risk Receiving Premedication Before Contrast-Enhanced CT - Mervak, Benjamin M.; Davenport, Matthew S.; Ellis, James H.; Cohan, Richard H. (American journal of roentgenology (1976), 2015)
The purpose of this study was to determine the rate of allergiclike breakthrough reactions among inpatients at high risk receiving premedication before undergoing CT with IV iodinated low-osmolality contrast material (LOCM). Inpatients (n = 1051) completing a 13-hour corticosteroid and diphenhydramine premedication regimen before LOCM-enhanced CT from January 1, 2010, through December 31, 2013, were included in the study. Breakthrough reaction rates were compared with the ordinary allergiclike reaction rate in the general population (0.6% [545/84,928]) by use of chi-square tests. Multivariate logistic regression was performed. Number needed to treat (NNT) was calculated for patients premedicated for a previous contrast reaction. Sixty percent (626/1051) of premedicated patients had had a previous reaction to iodinated contrast material, and 40% (425/1051) were premedicated for other reasons. The overall breakthrough reaction rates were 1.2% (13/1051) (p < 0.0001 vs the general population), 2.1% (13/626) for those with a previous iodinated contrast reaction (p < 0.0001), and 0% (0/425) for those premedicated for other reasons (p = 0.18). There were no severe breakthrough reactions. Younger age (p = 0.046; odds ratio, 1.03 per year; 95% CI, 1.001-1.07) and multiple indications for premedication (p < 0.0001; odds ratio, 2.7 per indication; 95% CI, 1.5-4.8) significantly increased the likelihood of a breakthrough reaction. The estimated NNTs were 69 (95% CI, 39-304) to prevent a reaction of any severity and 569 (95% CI, 389-1083) to prevent a severe reaction. Patients premedicated for a previous reaction to iodinated contrast material have a breakthrough reaction rate 3-4 times the ordinary reaction rate in the general population. Patients receiving premedication for other reasons have a breakthrough reaction rate near 0%. Many patients must receive premedication to prevent one reaction.